Differences in DNA Methylation Reprogramming Underlie the Sexual Dimorphism of Behavioral Disorder Caused by Prenatal Stress in Rats - Lei, Lei; Wu, Xinmiao; Gu, Hanwen; Ji, Muhuo; Yang, Jianjun (Frontiers in Neuroscience, 2020)
Prenatal stress (PS) can lead to neuroendocrine and emotional disorders later in adolescence. Sexual dimorphism in these neurodevelopmental outcomes have been observed; however, the underlying mechanisms are not fully understood. To address this issue, we investigated whether there are sex differences in epigenetic reprogramming in rats exposed to PS. Pregnant female rats were subjected to chronic restraint stress from gestational day (G)12 to G18. From postnatal day (P)38 to P45, subgroups of offspring including both males and females were subjected to behavioral testing and brain tissue specimens were analyzed by DNA pyrosequencing, western blotting, and Golgi staining to assess changes in DNA methylation patterns, expression of DNA methylation-related proteins, and dendrite morphology, respectively. The DNA methyltransferase (DNMT) inhibitor decitabine was administered to rats prior to PS to further evaluate the role of methylation reprogramming in the sexually dimorphic effects of PS. The results showed that PS increased anxiety-like behavior in offspring, especially in females, while depression-like behavior was increased in male offspring compared to control littermates. The methylation pattern in the promoter region of the glucocorticoid receptor gene differed between males and females. Sex-specific changes in the expression of DNMTs (DNMT1 and DNMT3a) and DNA demethylase (Tet methylcytosine dioxygenase 2) were also observed. Interestingly, decitabine alleviated the behavioral disorder caused by PS and restored dendrite density and morphology in female but not male rats. These findings suggest that distinct mechanisms of DNA methylation reprogramming in the 2 sexes are responsible for the sexually dimorphic effects of PS, which could have implications for the clinical management of stress-related disorders.